Academic achievement of junior high school students with sleep disorders - Fijri Auliyanti; Rini Sekartini; Irawan Mangunatmadja (Paediatrica Indonesiana, 2015)
Background Sleep disorders are prevalent in adolescents and may influence their academic achievement. To date, no study has been done in Indonesia on academic achievement in students with sleep disorders and its related factors. Objective To assess for relationships between academic achievement and related factors, including gender, motivation and learning strategies, IQ level, maternal educational level, socioeconomic status, family structure, after-hours education program, presence of TV/computer in the bedroom, sleep duration during school days, as well as bedtime and wakeup time difference in junior high school students with sleep disorders. Methods This cross-sectional study was performed from January to March 2013. Subjects were students from five junior high schools in Jakarta who fulfilled the criteria for sleep disorders based on the Sleep Disturbance Scale for Children questionnaire. Results There were 111 study subjects. The prevalence of sleep disorders was 39.7%, mostly in difficulties initiating and maintaining sleep (70.2%). Below-average academic achievement was seen in 47.6% of subjects. Factors significantly related to below-average academic achievement were after-hours education program (prevalence ratio 5.6; 95%CI 1.36 to 23.18; P = 0.017), average IQ level (prevalence ratio 3.26; 95%CI 1.38 to 7.71; P = 0.007), and male gender (prevalence ratio 2.68; 95%CI 1.06 to 6.78; P = 0.037). Conclusion Among junior high school students with sleep disorders, factors related to below-average academic achievement are afterhours education program (more than 2 types), the average IQ level, and male gender.